Toxicity of Substance BKP-115 on Rats and Mice of Both Sexes at Long Term Intragastric Introduction - Bigdan, O.; Бігдан, Олексій Антонович (My University, 2021)
Today there is a large number of scientific publications in which the heterocyclic systems of 1,2,4-triazole and their derivatives are studied. Many of the medications, which contain compounds with the 1,2,4-triazole ring, were discovered and applied in practice. For many years, 1,2,4-triazole derivatives remain the object of close attention of scientists of various scientific fields. The unique properties of 1,2,4-triazole derivatives include high reactivity, which allows different modification of this system, practical absence of toxicity of these derivatives, and the presence of a wide range of biological and pharmacological properties. For our research, we find the most promising compound for the study of acute toxicity. There is BKP-115, which shows interesting results in the classification of substances for toxicity class IV-V. The purpose of the work is to study the toxicity of substance BKP-115 on rats and mice of both sexes at long-term intragastric introduction, macroscopic examination of internal organs, and histostructure of internal organs.
Keywords: Derivatives of 1,2,4-triazole; BKP-115; Acute toxicity; Histostructure of internal organs